2016
DOI: 10.1080/09637486.2016.1189886
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of procyanidins B2 attenuates photooxidation-induced apoptosis in ARPE-19 cells

Abstract: During the aging process, dimers of dietary vitamin A accumulated in retinal pigment epithelium (RPE) cells. Vitamin A dimer-mediated photooxidation resulted in RPE apoptosis, which is associated with age-related degenerative disease of retina, leading to blindness. It has been reported that proanthocyanidin-rich grape seed extract reduces oxidative stress in the eye. In this study, we investigated the underlying mechanism of photooxidation-induced apoptosis inhibition by procyanidins B2 (PB2), one of the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Therefore, we found that OPC can inhibit apoptosis by protecting mitochondria. Similar results have been proven in other kinds of cells (39)(40)(41)(42)(43). In this study, we used chondrocytes derived from mice and did not compare with chondrocytes of other animals.…”
Section: Discussionsupporting
confidence: 73%
“…Therefore, we found that OPC can inhibit apoptosis by protecting mitochondria. Similar results have been proven in other kinds of cells (39)(40)(41)(42)(43). In this study, we used chondrocytes derived from mice and did not compare with chondrocytes of other animals.…”
Section: Discussionsupporting
confidence: 73%
“…Li et al . 36 also showed that the intervention of procyanidins B2 could significantly reduce the apoptosis of ARPE-19 cells induced by photooxidation, increase the proportion of bcl-2/Bax in mitochondria, reduce the release of ROS and cytochrome c, and reduce the caspase cleavage. Li et al .…”
Section: Discussionmentioning
confidence: 90%
“…The experimental results showed that the grape seed procyanidin B2 pretreatment could significantly reduce the apoptosis of renal tubular epithelial cells in mice and necrosis, and could significantly reduce the cleaved-caspase3 protein expression level; those might be related to grape seed procyanidin B2 pretreatment to enhance the overall antioxidant system in mice, at the same time reduce the ischemia-reperfusion kidney partial oxidative stress injury. Li et al 36 also showed that the intervention of procyanidins B2 could significantly reduce the apoptosis of ARPE-19 cells induced by photooxidation, increase the proportion of bcl-2/Bax in mitochondria, reduce the release of ROS and cytochrome c, and reduce the caspase cleavage. Li et al 37 also found that the antioxidant activity of grape seed proanthocyanidin B2 (GSPB2) and resveratrol inhibited the activation of cytochrome c release, caspase-9 and caspase-3 through the regulation of lactadherin, and had a protective effect on advanced glycation end products induced apoptosis.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Some exogenous substances, such as heavy metals and mycotoxins, induce endoplasmic reticulum stress and unfolded protein reactions that can result in apoptosis [24,31,33]. Studies have shown that some antioxidants such as resveratrol, procyanidin, and curcumin can inhibit apoptosis through inhibition of ERS [34][35][36]. Therefore, antioxidants can reduce the damage caused by foreign substances to cells by regulating endoplasmic reticulum stress.…”
Section: Introductionmentioning
confidence: 99%